PENDEKATAN KONSTRUKTIVISME DALAM PEMBELAJARAN MATEMATIKA - Amir, Almira (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
Constructivism approach is a concept that many talk about mathematic and is expected to become the intellectual foundation to develop and analyze mathematical learning problems. Pendekatan constructivism is one of the alternative settlement and expected as an activity undertaken in mathematics learning in order to become better and more effective so that students will achieve better result. In applying the approach of constructivism in mathematic learning, the teacher really have to pay attention to the environmental conditions for students and student’s readiness to learn, because it is as a means of interaction for them, and require attention eamest for theacher.